2013
DOI: 10.1002/jmv.23836
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in human leukocyte antigens, human platelet antigens, and cytokine genes in hantavirus cardiopulmonary syndrome patients from Ribeirão Preto, Brazil

Abstract: Hantavirus cardiopulmonary syndrome is a severe human disease associated with hantavirus infection. The clinical course of illness varies greatly among individuals, possibly due to viral and immunological elements and the influence of host genetic factors on clinical outcome. As the magnitude of immune activation has been associated with disease severity, polymorphisms in genes involved in the immune response that may affect the development of this syndrome were investigated. Polymorphisms in the TGF-β, IL-10,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…96,102 Host factor such as HLA B*35 have been associated to an increased risk for severe HCPS outcomes. 103 During convalescence in patients with severe HCPS viral genome can be detected up to 90 days after the onset of clinical symptoms. 96 Hantaviruses can cause two zoonotic diseases in humans: HFRS or HCPS.…”
Section: Hantavirus Cardiopulmonary Syndrome and Hemorrhagic Fever With Renal Syndromementioning
confidence: 99%
“…96,102 Host factor such as HLA B*35 have been associated to an increased risk for severe HCPS outcomes. 103 During convalescence in patients with severe HCPS viral genome can be detected up to 90 days after the onset of clinical symptoms. 96 Hantaviruses can cause two zoonotic diseases in humans: HFRS or HCPS.…”
Section: Hantavirus Cardiopulmonary Syndrome and Hemorrhagic Fever With Renal Syndromementioning
confidence: 99%
“…In this phase, the disease can rapidly progress to multiorgan failure, and death may occur within 24 hours [ 25 ]. Disease pathology, which is characterized by microvascular leakage, is mainly attributed to host immune response, illustrated by the fact that infection of endothelial cells does not lead to cytopathology [ 26 , 27 ]. Viral load does not appear to predict the severity of clinical presentation [ 3 ].…”
Section: Case Reportsmentioning
confidence: 99%
“…Several studies have suggested that host genetic constitution may influence the clinical outcome of hantavirus infection, resulting in mild or severe disease [16,17,18,19,20,21]. In HCPS patients, HLA-B*08 and HLA-DRB1*15 alleles were associated with disease severity, as well as polymorphisms in the IL28B gene [17,22].…”
Section: Introductionmentioning
confidence: 99%